Expression of Notch1 in Ameloblastoma and Correlation with CBCT Imaging Subtypes - Gabiyatu, Baoyinbatu; Li, Wenchao; Wurihan; Tian, Yuan; Baasandorj, Lkhagvasuren; Li, Senhao; Tsagaankhuu, Sarnai; Boldbaatar, Damdindorj (Central Asian Journal of Medical Sciences, 2023)
Objective: Ameloblastoma (AM) is a prevalent benign odontogenic tumor affecting the jaw bone. Its potential for recurrence and malignant transformation is closely associated with the regulation of signaling pathways. The objective of this study was to examine the expression and clinical significance of Notch1 in AM, along with exploring the correlation between Notch1 expression and AM imaging patterns. Methods: The streptavidin-peroxidase (S-P) immunohistochemical technique was employed to detect the expression of Notch1 protein in the oral mucosa of 70 AM patients and 25 normal controls. Additionally, the preoperative cone-beam computed tomography (CBCT) images of the patients were classified, and the results were analyzed in relation to the expression of Notch1 protein in AM. Results: The positive expression rate of Notch1 in the 70 AM patients was 74.29% (52/70), while the Notch1 expression rate in 26 oral mucosa patients was 19.23% (5/26), indicating a statistically significant difference (P < 0.05). The expression rate of Notch1 was 58.06% in single-room AM and lower in multi-room AM (85.29%) and honeycomb AM (100%) (P < 0.01). However, there was no significant difference in the expression rate of Notch1 between multi-room AM and honeycomb AM (P > 0.05). Conclusion: Notch1 may serve as an important diagnostic indicator in AM, and the apoptosis inhibition ability and cell proliferation ability of single-room AM are lower compared to those of the room and honeycomb types